'A society of rooms'. (Architects' Journal)
IN PRACTICE Stephen Bates, co-founder of Sergison Bates architects,discusses the thinking behind the practice's recent mansionblock project in Hampstead, designed for older residents Chronology We were invited by PegasusLife, whichspecialises in residential developments forolder people (aged 60+) to bid for a site inHampstead, which we won in 2014. The plan that emerged has acellular structure with no apparent hierarchyof rooms: apartments spin out from a middleroom at the centre - a multi-sided, generallyoctagonal room. In mid-2015we submitted to planning a designinspired by the mansion blocks typical ofHampstead, with two structures connectedat ground and lower floor level, providing29 large apartments, a basement spa andexternal garden.